2021
DOI: 10.1503/jpn.200080
|View full text |Cite
|
Sign up to set email alerts
|

Association between depressive symptoms and pulse wave velocity is mediated by increased adiposity in older adults with type 2 diabetes

Abstract: Background: Studies investigating the association between depression and aortic stiffness in older patients with type 2 diabetes are lacking. We postulated an association between depressive symptoms and aortic stiffness, and this relationship may be mediated by increased adiposity. Methods: We analyzed participants with type 2 diabetes aged 55 years or older (n = 958). We measured aortic stiffness using carotid-femoral pulse wave velocity (cut-off ≥ 12 m/s) using the tonometry method. We defined depressive sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Additional analysis tests GDS as a binary variable, with a score of 5 or higher constituting depressive symptoms. 20 - 24 …”
Section: Methodsmentioning
confidence: 99%
“…Additional analysis tests GDS as a binary variable, with a score of 5 or higher constituting depressive symptoms. 20 - 24 …”
Section: Methodsmentioning
confidence: 99%
“…13 In 2021, Moh et al discovered that older individuals with type 2 diabetes exhibit elevated pulse wave velocity in correlation with depressive symptoms. 14 A study in population-based by Nilsson et al also found that cognitive function showed an inverse relationship with pulse wave velocity, displaying a nonlinear pattern. 15…”
Section: Introductionmentioning
confidence: 96%